Use of methods for determining cell viability in cryobiological research - Sukach, Oleksandr; Maiorova, Olga (Problems of Cryobiology and Cryomedicine, 2026)
Assessment of cell viability is critically important in the context of cryobiological research, as it allows determining the effectiveness of freeze-thawing procedures and low-temperature storage of isolated cells. The review systematizes the methods for determining cell viability used in cryobiological research, with an emphasis on their practical applicability, accuracy, and sensitivity. Both traditional methods based on the assessment of cell membrane integrity and metabolic activity, such as trypan blue staining, MTT assay, fluorescent dye assays, and more modern approaches, including flow cytometry, confocal microscopy, and methods for assessing cell functional activity, are reviewed. For each method, a description of the mechanism of action, a protocol, specific advantages, disadvantages, as well as equipment requirements and limitations for cell types are provided. A comparative analysis was conducted, which revealed the lack of a universal approach, but demonstrated the effectiveness of combined methods that combine fluorescent staining and metabolic assessment. Such combinations allow for high accuracy in assessing cell viability after cryopreservation. In addition, the review discusses the prospects for the development of methods for determining cell viability in cryobiology, including the introduction of the latest high-resolution imaging technologies, multiparametric analysis, as well as integration with microfluidic platforms and artificial intelligence to automate and improve the accuracy of the assessment. The review can serve as a practical tool for researchers in choosing the most optimal approach for assessing cell viability depending on the purpose of the experiment, available resources and cell type. Probl Cryobiol Cryomed. 2025; 35(4): 179—193